Infant feeding experiences among Indigenous communities in Canada, the United States, Australia, and Aotearoa: a scoping review of the qualitative literature - Hiliary Monteith; Carly Checholik; Tracey Galloway; Hosna Sahak; Amy Shawanda; Christina Liu; Anthony J. G. Hanley (BMC, 2024)
Abstract Background Although exclusive breastfeeding is recommended for the first six months of life, research suggests that breastfeeding initiation rates and duration among Indigenous communities differ from this recommendation. Qualitative studies point to a variety of factors influencing infant feeding decisions; however, there has been no collective review of this literature published to date. Therefore, the objective of this scoping review was to identify and summarize the qualitative literature regarding Indigenous infant feeding experiences within Canada, the United States, Australia, and Aotearoa. Methods Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses- Scoping Reviews and the Joanna Briggs Institute Guidelines, in October 2020, Medline, Embase, CINAHL, PsycINFO, and Scopus were searched for relevant papers focusing on Indigenous infant feeding experiences. Screening and full-text review was completed by two independent reviewers. A grey literature search was also conducted using country-specific Google searches and targeted website searching. The protocol is registered with the Open Science Framework and published in BMJ Open. Results Forty-six papers from the five databases and grey literature searches were included in the final review and extraction. There were 18 papers from Canada, 11 papers in the US, 9 studies in Australia and 8 studies conducted in Aotearoa. We identified the following themes describing infant feeding experiences through qualitative analysis: colonization, culture and traditionality, social perceptions, family, professional influences, environment, cultural safety, survivance, establishing breastfeeding, autonomy, infant feeding knowledge, and milk substitutes, with family and culture having the most influence on infant feeding experiences based on frequency of themes. Conclusions This review highlights key influencers of Indigenous caregivers' infant feeding experiences, which are often situated within complex social and environmental contexts with the role of family and culture as essential in supporting caregivers. There is a need for long-term follow-up studies that partner with communities to support sustainable policy and program changes that support infant and maternal health.